Electrochemical behavior study of sodium saccharin in an aqueous electrolyte solution by a nano-sensor, using cyclic voltammetric technique - Radhi,Muhammed M. (2021)
Abstract This study investigated one of the chemical compounds taken by diabetic patients as a replacement for natural sugar. Its aim was to identify the electrochemical properties of sodium saccharin in different electrolytes, using a nano-sensor. Sodium saccharine was studied by cyclic voltammetric technique, in different electrolytes, using a modified glassy carbon electrode (GCE) with carbon nanotubes (CNT) as working electrode (CNT/GCE). It was found that the redox current peaks of 0.01 mM sodium saccharine in 1 M Na2SO3 enhanced both redox peaks with the CNT electro-catalyst on the GCE surface. Different concentrations, pH and scan rates of sodium saccharine in Na2SO3 have been studied. Also, the nano sensor showed good reliability and stability towards the chemical compounds in the cyclic voltammetric cell. Other electrochemical parameters were determined, such as the potential peak separation (Epa-Epc≈100 mV), the current ratio (Ipa/Ipc≈1) of the redox peaks and the cathodic-anodic reaction rate. The diffusion coefficient value was determined at different scan rates.